POTENTIAL CHANGE IN RUSSIA’S POSITION IN THE GLOBAL GAS MARKET AS THE OPTIMIZATION OF THE LOCAL ENERGY SECURITY MODEL - KREJDENKO, Tatyana; ADASHOVA, Tatyana; MELANINA, Maria; KORENEVSKAIA, Anna (CENTRAL ASIA AND THE CAUCASUS, 2017)
Today, ensuring energy security is one of the key tasks for every state, whether it is a net exporter, net importer, or a transit country. With regard to the EU countries, the declaration of energy security as the priority issue of energy policy is largely due to low endowments of their own reserves of hydrocarbon resources and hence a high dependence on the suppliers of energy resources. As it happens, the EU’s own natural gas production is able to supply only 35% of the aggregate demand, with the rest being provided by Russia, Norway, Algeria, and Qatar. Since about a third of the total volume of gas imports comes from Russia, it creates a de facto dominant position of the Russian Federation in the EU gas market. The study of the transportation aspect of energy security of the EU has become a particularly relevant subject since the escalation of the political crisis in Ukraine in 2014-2016. In the current circumstances, there remain uncertainties regarding the prospects of the Russian gas deliveries to the EU countries through the territory of Ukraine and, in consequence, the question of transportation, as a component of the gas market, has become one of the most important on the agenda of the EU on the subject of cooperation with Russia. The problem of energy security becomes even more acute due to the actions of energy companies of the exporting countries, seeking to obtain access to the gas end-user and attempting to acquire equity shares in companies involved in transportation and sales. These attempts are met with resistance on the part of the supranational agencies of the EU, which is reflected in the adoption of relevant legislative acts. The prospects for maintaining gas exports from Russia are significantly influenced by the vigorous actions of the EU countries on the implementation of energy-efficient technologies and the wider use of renewable sources of energy. Thus, the analysis of potential changes in the strategy of the EU countries in the context of contemporary trends for strengthening the energy security in the gas market is particularly important for improving the export strategy of Russia in this market.